Elements of the Cognitive Sovereignty Strategy in Arctic Socio-Humanitarian Research - Elena V. Kudryashova; Artem V. Makulin; Marina V. Nenasheva; Inga M. Zashikhina; Larisa A. Zhgileva; Fen Lyu; Sun Yanan (Арктика и Север, 2025)
The article discusses the elements of the concept of “cognitive sovereignty” in relation to the practice of building a unified Russian strategy in Arctic socio-humanitarian research. Based on the problem field of various types of sovereignty, the general outlines of a strategy for creating an integrated mechanism for independent examination of existing and future scientific concepts that define thematic, problematic and methodological diversity in Arctic socio-humanitarian research are highlighted. The proposed strategy explicates the close relationship between the level of formation of cognitive sovereignty in the Russian humanitarian scientific community and the possibilities of developing the domestic potential of a cognitive resource in the social sciences. The authors are of the opinion that the production, functioning and transformation of the content of knowledge are socially determined; therefore, cognitive sovereignty is considered as a tool that prevents the ideological and informational manipulation of cognitive intents of Russian science. The practical significance of the proposed strategy lies in the possibility of applying its provisions in the development, planning and implementation of socio-humanitarian scientific research, providing Russia with the opportunity to create not only innovative ideas and products, but also to make them globally competitive. The latter is a guarantee of an independently manageable and understandable future, defense capability, economic power and the possibility of successful competition in the Arctic region.